Discrimination and disparities - Sowell, Thomas, 1930- (New York : Basic Books, 2019)
"In this new, revised and enlarged edition, Discrimination and Disparities goes beyond its analysis--in the first edition--of the sources of disparities and the different kinds of discrimination. It deals with undeniable fact of gross disparities in opportunity, without succumbing to the 'social justice' vision of our time--a vision with demonstrably false assumptions, and solutions that may not even be possible, in any comprehensive and sustainable sense. Instead, some more modest but feasible options are examined."--Dust jacket.
Disparities and prerequisites -- Discrimination: meanings and costs -- Sorting and unsorting people -- The world of numbers -- The world of words -- Social visions and human consequences -- Facts, assumptions and goals.
"Originally published in hardcover and ebook by Basic Books in March 2018"--Title page verso.
Includes bibliographical references (pages 229-282) and index.
Keywords: Income distribution; Discrimination -- Economic aspects; Minorities -- United States -- Economic conditions; Minorities -- Economic aspects -- United States; Race discrimination -- United States